2006
DOI: 10.2134/agronj2005.0070
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Meter Readings Can Predict Nitrogen Need and Yield Response of Corn in the North‐Central USA

Abstract: Nitrogen fertilizer is a fundamental input for production of corn (Zea mays L.) that can move to ground and surface waters when overapplied. Previous research has shown that chlorophyll meter (CM) readings can indicate N stress in corn, but has not addressed whether the amount of N needed can be predicted by CM readings. Our objective was to evaluate whether CM readings can predict corn N need and yield response to N. Sixty-six N rate experiments were conducted in seven north-central states over a 4-yr period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
133
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 38 publications
12
133
0
2
Order By: Relevance
“…Furthermore, they noted that when the sufficiency index at V8 was below 90%, maximum yields were not achieved with in-season N fertilizer applications, in part because early season N was below that needed for optimum growth and yield potentials had already been reduced. In another study involving 66 N rate experiments conducted in seven north-central states in the U.S. over a 4-year period, Scharf et al (2006) found that CM readings at all growth stages from V5 to R5 were significantly correlated with the economically optimal N rate and yield response to N applied at growth stage V7 or earlier. They concluded that CM readings are a good predictor of corn yield response to N over a wide range of soil types, geography, landscape forms, weather environments, corn hybrids, and management practices, and would be useful in making N-fertilizer management decisions.…”
Section: Leaf Chlorophyll Meter Sensingmentioning
confidence: 96%
“…Furthermore, they noted that when the sufficiency index at V8 was below 90%, maximum yields were not achieved with in-season N fertilizer applications, in part because early season N was below that needed for optimum growth and yield potentials had already been reduced. In another study involving 66 N rate experiments conducted in seven north-central states in the U.S. over a 4-year period, Scharf et al (2006) found that CM readings at all growth stages from V5 to R5 were significantly correlated with the economically optimal N rate and yield response to N applied at growth stage V7 or earlier. They concluded that CM readings are a good predictor of corn yield response to N over a wide range of soil types, geography, landscape forms, weather environments, corn hybrids, and management practices, and would be useful in making N-fertilizer management decisions.…”
Section: Leaf Chlorophyll Meter Sensingmentioning
confidence: 96%
“…6); (v) high and variable N prices; and (vi) cross-state agency programs, crop advisors, and producers desiring uniform recommendations across state boundaries. Of most importance was the poor correlation between yield-goal-based rate recommendations and optimal rates found in research trials; long-term research from the 1970s to the 1990s indicated that optimal N rates had not changed despite yield increases ; and yield level was found to be unrelated to EONR Bundy, 1994a, 1994b;Lory and Scharf, 2003;Scharf et al, 2006a).…”
Section: The Maximum Return To Nitrogen Approachmentioning
confidence: 99%
“…The latter application is of use mainly when manure N is part of the N supply, creating a significant proportion of fields where the correct decision is "no additional N needed". Systems for making N rate decisions based on chlorophyll meter readings were later developed by Scharf et al (2006a), Hawkins et al (2007), and Varvel et al (2007). The relationships between relative chlorophyll meter reading and optimal N rate (or suggested N rate) are similar for these three references, suggesting that these sets of available interpretations are robust.…”
Section: Sensing Spectral Properties For Nitrogen Recommendations Formentioning
confidence: 99%
“…Additionally, the experimental design for that research did not include the necessary N treatments to calculate a precise optimal N rate, so tool performance evaluation was limited. In another study, a wide range of soil and weather environments may have been explored, but only one N management decision tool was evaluated (Scharf et al, 2006).…”
mentioning
confidence: 99%